1999
DOI: 10.1210/jcem.84.7.5864
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Physiological Significance of Plasma Dopamine Sulfate

Abstract: Dopamine in the circulation occurs mainly as dopamine sulfate, the sources and physiological significance of which have been obscure. In this study, plasma concentrations of dopamine sulfate were measured after a meal, after fasting for 4 days, and during i.v. L-DOPA, nitroprusside, or trimethaphan infusion in volunteers; after dopamine infusion in patients with L-aromatic-amino-acid decarboxylase deficiency; in arterial and portal venous plasma of gastrointestinal surgery patients; and in patients with sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…Other in vitro studies have demonstrated the formation of hydroxytyrosol as a result of 3,4-dihidroxyphenylacetaldehyde (DOPAL), a dopamine metabolite, reduction by the human liver alcohol dehydrogenase isoenzyme (Mardh & Vallee, 1986). Tyrosine derived from the breakdown of dietary protein could be a precursor of endogenous formation of dopamine in cells containing the tyrosine hydroxylase enzyme (Goldstein et al, 1999). Therefore, endogenous formation of hydroxytyrosol could be derived from the human metabolism of dietary tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies have demonstrated the formation of hydroxytyrosol as a result of 3,4-dihidroxyphenylacetaldehyde (DOPAL), a dopamine metabolite, reduction by the human liver alcohol dehydrogenase isoenzyme (Mardh & Vallee, 1986). Tyrosine derived from the breakdown of dietary protein could be a precursor of endogenous formation of dopamine in cells containing the tyrosine hydroxylase enzyme (Goldstein et al, 1999). Therefore, endogenous formation of hydroxytyrosol could be derived from the human metabolism of dietary tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential in the presystemic elimination of dietary dopamine and other catecholamines. Moreover, gut SULT1A3 appears to be responsible for the metabolism of circulating dopamine (23). The identification of SULT1A3 in the brain, including dopaminergic regions of the midbrain (24), raises the possibility that it has a role in eliminating dopamine in the brain as well.…”
mentioning
confidence: 99%
“…This 13-member enzyme family transfers the sulfuryl moiety (-SO 3 ) from the universal donor 3Ј-phosphoadenosine 5Ј-phosphosulfate (PAPS; or activated sulfate) to the hydroxyls and primary amines of hundreds, perhaps thousands of acceptors (metabolites, drugs, and other xenobiotics) (1)(2)(3)(4). Sulfonation of small molecule activators of steroid (1-3), thyroid (5), and dopamine receptors (4) typically weakens their receptor binding affinities beyond the point of physiological relevance (6).…”
mentioning
confidence: 99%